Children and Youth in Low‐ and Middle‐Income Countries: Toward An Integrated Developmental and Intervention Science. (9th February 2015) - Wuermli, Alice J.; Tubbs, Carly C.; Petersen, Anne C.; Aber, J. Lawrence
Abstract In this article, we discuss the need for and value of an integrated developmental intervention science in low‐ and middle‐income countries (LAMICs), and the extent to which this integration of basic developmental science has influenced research on child and youth development interventions in these countries. We also consider how a global developmental science can be advanced by capitalizing on the opportunities provided by cross‐cultural, interdisciplinary, experimental, and mixed methods approaches. We argue that designing and evaluating human developmental interventions in LAMICs present an opportunity for both research and policy. Testing contextualized developmental approaches through rigorously evaluated interventions yields the promise of finding more powerful and scalable solutions that can reach more children and youth worldwide. Moreover, a theoretically rich and methodologically rigorous understanding of how interventions effect change in diverse countries and contexts can contribute to the development of a truly global developmental science.